Space of Cross-Disciplinary Researches of Life, Nature and Society - Alina, Paranina (Journal of Biosemiotic Research, 2018)
Journal of Biosemiotic Research is a new periodical devoted to a young, actively developing science. A review of recent scientific publications shows that in the broad scientific space of biosemiotics contemporary questions and "eternal themes" interact, not finding an answer in the private sciences - anthropology, semiotics of culture and philosophy1,2. To solve them, the fundamental foundations of science and new achievements, the opportunities of the latest technologies and scientific communications are attracted. Like all young sciences, biosemiotics has many definitions. We give here the most famous ones. "Biosemiotics: (bios, life + semion = sign) is an interdisciplinary field of theoretical and empirical research, analyzing communication and signification in living systems. Signed processes, ranging from molecular to ecological and evolutionary, have been studied throughout the history of biology; however, very often descriptions of information and communication aspects of living systems were considered only metaphorical, believing that the essence of them can be understood with the help of physical and chemical descriptions. In biosemiotics, on the other hand, information sign processes are considered as the primordial, basic system of phenomena of life, requiring a new understanding..."3. "Biosemiotics explores sign systems of various levels: molecular biological (genetic code), intracellular (signal peptides), intercellular (mediators, immune interactions), intraorganism (hormones, conditioned reflex reactions) and interorganism (telergons, pheromones, attractants) ... In addition, biosemiotics covers all the problems associated with the problem of the existence of language and thinking in animals." However, today we can go further and add to the analysis the next stage of evolution, standing between animals and modern human (Homo sapiens sapiens).
Keywords: Biosemiotc; Anthropogenesis; Sapiyentation; Culture genesis; Solar energy and information.